Why does pain exist, how does it work, what can go wrong and how is it treated? - St. John Smith, Ewan (Henry Stewart Talks, 2019)
What pain is and why we need it, How pain is caused, Genetic conditions that cause abnormal pain sensation, Main therapeutic strategies for treating pain